Effect of Fiber Surface Modification on the Thermo-Mechanical Behaviour of Wood-Polymer Composite - Farsi, Mohammad (Asian Journal of Chemistry, 2012)
The effects of fiber surface modification on the thermo-mechanical behaviour of wood polypropylene composites have been studied. The filler was treated with different chemical components including: alkaline, silane, acrylic acid and benzoyl chloride. The samples were fabricated by melt compounding in an internal mixer and then injection molding. The structure of the treated sample was studied by FTIR spectroscopy and scanning electron microscopy. Dynamic mechanical thermal analysis was performed in the range of -50 to +150 °C and adhesion factor, storage modulus and mechanical loss factor (tan d) were recorded over the selected temperature range. The results showed that surface modification of wood flour decreased OH group intensity occurs on 3400 cm-1 band. It is found that with incorporation of wood to polypropylene the glass transition of the composites shifts to a higher temperature. The polypropylene composites made of silane treated wood showed the highest E' and tan d and lowest adhesion factor than the untreated ones. However, good correlations of chemical treatment and adhesion factor have been found for wood plastic composites, Further evidences of improved matrix-filler interactions is observed by scanning electron microscopy.